2023
DOI: 10.1186/s12984-023-01145-4
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality-based interventions for the rehabilitation of vestibular and balance impairments post-concussion: a scoping review

Abstract: Background Concussions and mild traumatic brain injuries are the most common causes of physical and cognitive disability worldwide. Concussion can result in post-injury vestibular and balance impairments that can present up to five years post initial concussion event, ultimately affecting many daily and functional activities. While current clinical treatment aims to reduce symptoms, the developing use of technology in everyday life has seen the emergence of virtual reality. Current literature h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…Specifically on the FGA both groups began on average at fall risk (below 22) and came closer to maximal score (on average 28 or 26 points out of 30) following the intervention. These changes of a little over 20% are similar to the ones reported in a recent systematic review [ 11 ]. There was a strong theoretical rationale to believe that an individualized, context-specific approach that allows for immersive training in standing and stepping would provide greater benefits for patients with vestibular dysfunction than off-the-shelf games.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Specifically on the FGA both groups began on average at fall risk (below 22) and came closer to maximal score (on average 28 or 26 points out of 30) following the intervention. These changes of a little over 20% are similar to the ones reported in a recent systematic review [ 11 ]. There was a strong theoretical rationale to believe that an individualized, context-specific approach that allows for immersive training in standing and stepping would provide greater benefits for patients with vestibular dysfunction than off-the-shelf games.…”
Section: Discussionsupporting
confidence: 88%
“…Technology ranging from off-the-shelf games to laboratory large screens has been used for many years in vestibular rehabilitation and has been shown to be effective with regards to physical outcomes and for facilitating sensorimotor relearning for balance [ 7 ] though not necessarily better than traditional rehabilitation [ 8 , 9 ]. Recent systematic reviews observed potential clinical benefits of virtual reality technology for vestibular rehabilitation compared with conventional vestibular rehabilitation based on low level of evidence [ 10 , 11 ]. Yet they noted a gap in the literature related to utility of newer portable headsets and the efficacy of an individualized, context specific approach that can be used to train balance when the patient is standing and moving [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation